Public policies of democratization of inclusive higher Education, at the Faculty of Psychological sciences of the UCE (2008-2018). - Romero Chico, Rosa Angélica; López Ortega, Antonieta Alexandra (SATHIRI, 2019)
Since 2011, admission was developed through the National Leveling and Admission System created as a democratizing public policy for access to inclusive higher education. Revealing the ineffective articulation in the step of baccalaureate to the university; for not considering mainly the diversity of origin of the applicants, the conditions of disability and equity, the dynamics of the family economy that entails the application of the admission strategy, the conditions of the redesign and / or closure of careers of interest. The study is carried out under a complex path, based on the inductive, analytical- synthetic methods, under the documentary review technique, without showing in the institution in consideration of the lack of records of students with disabilities. There have been no effective effective solutions, in this period it is stated that universities will be the ones that grant the quotas based on the places released, will be indispensable both the exam grade Be Bachiller and the note of the admission process. It is described: the implementation of the system in a general way and in a specific way xposes the experience and project of the Faculty of Psychological Sciences of the Central University of Ecuador, alma mater.